PENYALAHGUNAAN WEWENANG OLEH PEJABAT DIPLOMATIK DALAM MELAKSANAKAN TUGAS DIPLOMATIKNYA DITINJAU DARI ASPEK HUKUM INTERNASIONAL (Studi Kasus Penganiayaan Terhadap TKI oleh Duta Besar Arab Saudi di Jerman) - Hanna Safira Nasution; Chairul Bariah; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2017)
ABSTRACTOne form of cooperation between countries in the world is in the form of International Relations by placing diplomatic representation in various countries. This Diplomatic Representative has the right of immunity and privilege against the law of the receiving State Jurisdiction as well as civil and criminal immunity against witnesses. The purpose of this study was to find out the abuses of immunity and privileges committed by Saudi Arabian diplomatic officials against his personal servants in Germany. The normative method used in this study focuses on the legality of legal norms Positive immune rights and privileges granted by the Vienna Convention of 1961 to ensure the Implementation of diplomatic functions, but that does not mean diplomatic officials can be free To act in the recipient country. As a representative of the sending country, he shall respect the law and the rules of the receiving country (Article 41 paragraph 1 of the Vienna Convention of 1961). One of the Immunities enjoyed by diplomatic agents is the immunity from the criminal jurisdiction of State acceptance (Article 31 paragraph 1 of the Vienna Convention of 1961). If a diplomatic agent violates the laws and regulations of the receiving country, he can not be subject to sanctions under national law to accept the State because he enjoys immunity as found in Article 31 paragraph 1. In the case of 2009 Personality in Germany. The diplomat's private servant is an Indonesian migrant worker, named Dewi. Diplomat Of Saudi Arabia and his family did not pay wages according to agreement, Dewi was physically abused, and her passport was arrested. The actions of the diplomat and his family violated the provisions of Article 41 of the Vienna Convention of 1961. As the representative of the sending country (Saudi Arabia), the Diplomat could not be punished by German national law in chapter 31 verse 1 at the Vienna Convention of 1961. Keywords: Immunity and privilege, diplomatic officer, Vienna Convention of 1961